Assessment of quality of life in patients undergoing maintenance hemodialysis in a tertiary care hospital - Goyal, Aarnav; Sharma, Aarshi; Sharma, Pallavi; Bagal, Tamanna (International Journal of Research in Medical Sciences, 2025)
Background: The increasing prevalence of end-stage renal disease (ESRD) in India necessitates a deeper understanding of its impact on patient well-being. This study aimed to assess the quality of life (QOL) among hemodialysis (HD) patients in a North Indian setting using the kidney disease QOL-36 (KDQOL-36) instrument and to explore the associated demographic and clinical factors influencing their QOL. Methods: We conducted an observational, cross-sectional study over two months (May-June 2024) at a tertiary care hospital in Jammu, India. A total of 100 patients aged 18-75 years, diagnosed with ESRD and undergoing maintenance HD for at least three months, were included after providing informed consent. Data was collected using a demographic questionnaire and the validated KDQOL-36 instrument. Statistical analysis was performed using SPSS ver 25.0. Results: The study cohort comprised 100 patients (66% male) with a mean age of 58.08±12.3 years. The mean QOL scores indicated significant impairment across multiple domains: Physical component summary (PCS) was 41.19±8.24, mental component summary (MCS) was 42.52±7.84, symptom/problem list was 77.75±14.57, and effects of kidney disease was 56.56±16.48. The most profoundly affected domain was the burden of kidney disease, with an exceptionally low mean score of 24.00±15.24. A majority of patients reported that the disease interfered with their life (88%), felt like a burden to their family (74%), and were bothered by fluid (94%) and dietary (88%) restrictions. Conclusions: This study highlights a profound impairment in the QOL among HD patients in North India, particularly concerning the overwhelming burden of the disease. The findings underscore the urgent need for renal healthcare systems in India to integrate routine QOL assessments into standard practice. Shifting towards a more holistic, patient-centered approach that includes targeted psychosocial support is crucial to alleviate the immense disease burden and improve overall well-being in this vulnerable population.